Análisis de los avances en el tratamiento médico de la insuficiencia cardíaca. - Poma Auquilla, Jhoselyn Verónica (2025)
Heart failure (HF) is a leading cause of morbidity and mortality worldwide, with a significant impact in countries like Ecuador, where an aging population and cardiovascular risk factors increase the burden on the healthcare system. Despite therapeutic advances such as SGLT2 inhibitors, ARNIs, beta-blockers, vericiguat, MitraClip, and gene therapy, their implementation faces clinical, economic, and structural barriers. This systematic review, based on PRISMA guidelines and conducted using databases such as PubMed, Scopus, Cochrane, and ScienceDirect (2020–2025), analyzed the efficacy, safety, and clinical applicability of new therapies for HF. Sacubitril/valsartan and SGLT2 inhibitors showed reductions in hospitalizations and mortality. Vericiguat demonstrated benefits in patients with reduced ejection fraction HF after recent decompensation, though with variable efficacy across clinical subgroups. The MitraClip device improved outcomes in patients with functional mitral regurgitation and refractory HF. No studies were identified in the Ecuadorian population. In conclusion, while contemporary therapies represent significant progress, their adoption in Ecuador is limited by contextual factors. National research should be encouraged, and clinical guidelines should be adapted to local epidemiological and structural realities to optimize HF management.